O prazo razoável como direito humano de acesso à justiça no Mercosul - Ratkiewicz, Ana Carolina Machado (2006)
he jurisdictional protection in the appropriate time represents a human right, basis of Democratic States. Being the access to Justice a human right, translating into the citizenship exercise, it is necessary to improve the procedure technique, so that the judgment corresponds to the amounts and complexity of the demands present in the contemporary society, in their inner area as well as the integration process that they make part of. Considering these aspects, this research is structured in order to verify how the main innovations brought by the Olivos Document contribute to the fulfillment of the reasonable duration guarantee of judgment on its area. With the purpose of making it possible, it is used the dialectic method, in view of the variety of understandings concerning the subject and they are used the historical and typological methods in relation to the proceeding. The development of this research allows to state that the complete accomplishment of the constitutional guarantees only will be achievable through an authentic interpretation of the contemporary Civil Procedure, by solving the litigations in an efficient way in the appropriate time. In this context, it is possible to say that some different kinds of proceeding assume an important role in the search of procedure celerity, which contributes, consequently, for the effectiveness of judgment. As a general rule, it is possible to state that the innovations brought by the Olivos Document were responsible to keep the agility which qualifies the proceedings that exist in Mercosul area. Equally, it is necessary that the Review Permanent Court, institution, created by the referred Document, develops case laws regarding the subject matter, so as to bring about the complete observation to the reasonable duration guarantee on this integration process.